Vaccinating the economy against Covid-19: ex post revenue insurance for firms and households to sustain economic confidence and aggregate demand. Issue 1 (2nd January 2022) - Meade, Richard
Abstract : The Covid-19 pandemic risks causing a major collapse in 'economic confidence' – i.e. the beliefs of firms and households that all other firms and households will maintain their economic activity – and hence in aggregate demand. Economic responses like wage subsidies may prove inadequate for sustaining confidence due to their limited scope, and because their high cost makes them unsustainable. An alternative is ex post revenue insurance, enabling firms and households to borrow against their own future incomes to top up current pandemic-related income shortfalls. Making such loans repayable through future tax surcharges (along the lines of existing student loans schemes) is administratively feasible, and likely to be both more effective and affordable – and inter-generationally equitable – than existing support measures. Government pre-committing to making such loans available for as long as they are necessary should maintain economic confidence and aggregate demand, minimising the pandemic's economic harms.